Autobiographical memory functions: an emancipatory approach to construct environmental education outcomes. Issue 5 (3rd May 2020) - Wu, Meng; Zhu, Zhen; Chen, Jin; Niu, Lijuan; Liu, Chi-Chang
Abstract: In this study, we assessed how 34 young adult participants in an environmental education (EE) program from 2011 to 2014 constructed their learning outcomes through interviews and the exploration of autobiographical memory functions (AMFs) regarding program experiences. We articulated a variety of directive, social, and self AMFs, including the achievement of the top five typical objectives of EE, increase in positive social norms through reminiscing and sharing memories, and attainment of diverse personal growth. We also constructed the relationship of these outcomes with the ultimate objective of EE. This method can presumably be used to emergently construct outcomes for evaluating emancipatory EE programs, which are on the request of tackling wicked environmental problems.